Penerapan Kurikulum Merdeka sebagai Upaya Dalam Mengatasi Krisis Pembelajaran (Learning Loss) - Dwi Aryanti; M Indra Saputra (Universitas Hamzanwadi, 2023)
Research has been carried out on the application of Independet Curriculum as an effort to overcome the Learning Loss in Islamic Education subject at SMAN 12 Bandar Lampung. This research was conducted to provide good information to educational units, students as well as parents and even education stakeholders regarding a clear description of the characteristics offered by the independent curriculum which has comparisons with K-13 so as to provide solutions for the world of education to overcome the learning crisis that occurs at the moment. This type of research is field research using a qualitative approach. The method of data collection is through observation, interviews, and documentation. From the results of the study, it can be concluded that: First, Independent Curriculum Planning as an Effort to Overcome Learning Crisis (Learning Loss) in Class X PAI Subjects at SMAN 12 Bandar Lampung includes Planning. Second, the Implementation of the Independent Curriculum as an Effort to Overcome the Learning Crisis (Learning Loss) in Class X PAI Subjects at SMA N 12 Bandar Lampung. Third, Evaluation of the Independent Curriculum as an Effort to Overcome Learning Crisis (Learning Loss) in Class X PAI Subjects at SMAN 12 Bandar Lampung.